ANALYSIS OF PRODUCTION QUALITY CONTROL AT THE SMOKED TILAPIA MSMES USING THE SIX SIGMA METHOD WITH THE DMAIC APPROACH - Alfi Amalia Mahardiani; Inggit Marodiyah (Antis Publisher, 2025)
Objective: This research aims to determine the sigma value and factors that cause defects in the production process of Mujair Asap MSMEs and determine risk mitigation for product quality control at Mujair Asap MSMEs. Method: In this research, the method used is the Six Sigma method with the Define, Measure, Analyze, Improve and Control stages. Results: As a result of this research, it is known that the highest risk in the Mujair Asap MSME production process is defects in the form of shapes that do not comply with standards. Priorities for improvement are additional training for workers, creation of SOPs, suitability of the raw materials used and appropriate methods and equipment to support MSME productivity and minimize defects in the products produced. Novelty: An important factor in building a business is quality. Quality control is important to maintain consumer loyalty. In a production process, it is often found that the resulting product still does not comply with predetermined standards. In the Mujair Asap Business, the products produced often do not meet the appropriate standards, defective or damaged products result in significant losses if not immediately repaired.